External intervention and the politics of state formation : China, Indonesia, and Thailand, 1893-1952 - Chong, Ja Ian (Cambridge University Press, 2012)
"This book posits that when foreign actors face high opportunity costs of intervention in a weak state, their behavior may foster state sovereignty"--